The Role of Parents in Instilling Saving Habits to Shape Disciplined and Responsible Character in Children from an Early Age - Ririn Sefriany; Arfinda Sari; Muzimah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Amidst rapidly changing times, instilling the habit of saving in children from an early age has become increasingly relevant. Saving is not merely a financial activity; it is an integral part of character education that fosters discipline and responsibility. Parents, as a child's first and primary educators, play a crucial role in guiding them to understand the value of money and sound financial management. Through simple, visual approaches such as games and stories children can more easily grasp the concept of saving. Parental involvement in this process, including offering praise and setting savings goals, can boost a child's self-confidence and sense of responsibility. This study employs a qualitative method with a case study approach to examine the role of parents in instilling the habit of saving. The findings indicate that parental consistency and support significantly influence the development of a child's disciplined and responsible character, as well as their future financial readiness.